2024
DOI: 10.1101/2024.01.10.575001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Timing matters: A meta-analysis on the dynamic effect of stress on salivary immunoglobulin

Lennart Seizer,
Lukasz Stasielowicz,
Johanna Löchner

Abstract: The impact of psychological stress on physiological systems has been a focus of extensive research, particularly in understanding its diverse effects on immune system activity and disease risk. This meta-analysis explores the dynamic effect of acute stress on salivary immunoglobulin-A (S-IgA) levels, a key biomarker for secretory immunity within the oral environment. Analyzing data from 34 samples comprising 87 effect sizes and a total of 1,025 subjects, a multi-level approach is employed to account for the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This effect was moderated on a between-subject level by the individual emotion regulation skills with higher regulation competencies corresponding to a less positive association between negative emotions and S-IgA. These results fit to previous studies that found (i) acute psychosocial stress to lead to increased S-IgA levels (Seizer, Stasielowicz, et al, 2024), (ii) that this immunological response covaries with the level of negative emotions in response to adverse events (Aschbacher et al, 2012;Carroll et al, 2011;Puterman et al, 2014), and (iii) that the psychophysiological stress response may be moderated by emotion regulation skills (Jentsch & Wolf, 2020;Krkovic et al, 2018;Mikolajczak et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This effect was moderated on a between-subject level by the individual emotion regulation skills with higher regulation competencies corresponding to a less positive association between negative emotions and S-IgA. These results fit to previous studies that found (i) acute psychosocial stress to lead to increased S-IgA levels (Seizer, Stasielowicz, et al, 2024), (ii) that this immunological response covaries with the level of negative emotions in response to adverse events (Aschbacher et al, 2012;Carroll et al, 2011;Puterman et al, 2014), and (iii) that the psychophysiological stress response may be moderated by emotion regulation skills (Jentsch & Wolf, 2020;Krkovic et al, 2018;Mikolajczak et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…An explanation is that evolutionarily such states of adversity were often associated with potential injuries to the body and an anticipatory upregulation of immune function can help with wound healing and to battle infections (Marsland et al, 2017). Similarly, it has been shown that mucosal immunity is influenced by stress and emotions such as disgust or fear, for example, salivary immunoglobulin-A levels increase in response to acute stress and from the visual perception of disease-related content (persons sneezing and rotten food) (Keller et al, 2022;Schaller & Park, 2011;Seizer, Stasielowicz, & et al, 2024). A better understanding of the connection between emotions and immune responses is essential because it could point to modifiable mechanisms via which psychosocial influences regulate immune system activity (Graham- Engeland et al, 2018;Khandaker et al, 2021).…”
Section: Introductionmentioning
confidence: 99%